(3OjhGf GdMGLQjs - (3MSGe GdOjf Hf YjSi Hf SfLQ Hf HgQGe Hf LHQjd GdEQHdj GdeYQha H` GdMGLQi,J (B639 (3g` s
(3ChdgG (B:s
(3bGd GdCejQ GdHGQY GdeYQha HGdMGLQj hcGfJ haGJg bGd GdeDda dgPG GdOjhGf (B((3GdLGeY dg(B) (3hgh SHjd GdhGba Ydi gPG GdOjhGf GdUaM YeG jLOg ef GdNWC hGdRdd s
(3BNQgG (B:s
(3dj ajc, hEf cKQ ajc dYPd bdH Ofa hCOeY Jfged efUGQ LeGdg GdeaOi eKdG bO UGQ HhLOj aj ghGg GdeKd s
(3eVHhWI HGdTcds
(3hJfbU GdaUd GdSGHY eG bGdg ef GdehGdjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B70 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B783s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs